KOMITMEN INDONESIA PADA KTT G20 ARAB SAUDI DAN PEMBANGUNAN NASIONAL: SEBUAH TINJAUAN KOMPREHENSIF - Gema Ramadhan Bastari; Semmy Tyar Armandha; Dicky Adiatma; Xandra Leonora; Rizma Afian Azhiim; Nadia Zahara (Review of International Relations, 2022)
This study examines the usefulness of commitments in G20 Riyadh Summit Leaders’ Declaration for Indonesian national development. The analytical method applied in this study consists of mapping analysis, qualitative text analysis, and critical discourse analysis. Through the three sets of analytical methods, this study develops three key identifications. First, identification of commitments in G20 Riyadh Summit Leaders’ Declaration which substantially contains the development agenda. Second, identification of commitments in G20 Riyadh Summit Leaders’ Declaration that are concomitant and in accordance with Indonesia's development priorities. Third, identification of commitments in development issue that urged to be implemented through diplomacy. The three identifications indicate at least two findings. First, 'synchronization', adjustments between the global agenda and policies, both policies that have been set and policies that have been formulated. Second, balance of national interests with values ​​that are considered as the Global Common Goods.